What’s It Like to Be White?: Understanding the Decision to Learn About Being White - Marguerite A. Welch (Adult Education Research Conference, 2014)
As a dominant social identity, whiteness is often not visible to white people. Developing a nuanced understanding of whiteness, including the systemic nature of white supremacy, is essential for white adult educators who want to create inclusive learning environments.